Distribution of Vibrio species in Shellfish and Water Samples Collected from the Atlantic Coastline of South-East Nigeria (Journal of Health, Population and Nutrition, 2013)
Crayfish, lobster, and sea-water samples collected from five fishing islands on the Atlantic coastBight of Biafra (Bonny)belonging to Ibaka Local Government Area of Akwa-Ibom State of Nigeria were bacteriologically evaluated on thiosulphate citrate bile-salt sucrose (TCBS) agar for Vibrio load and pathotypes. Mean log10 Vibrio counts of 7.64}2.78 cfu/g (in crayfish), 5.07}3.21 cfu/g (in lobster), and 3.06}2.27 cfu/mL (in sea-water) were obtained in rainy season (June-July) while counts in the dry season (November-December) were 6.25}1.93 cfu/g, 5.99}1.54 cfu/g, and 3.84}1.78 cfu/mL respectively. The physicochemical measurements (temperature, pH, and total dissolved solutes) of the sea-water did not vary significantly in the two seasons across all five islands. Vibrio species isolated were Vibrio cholerae (both O1 and non-O1 serotypes), V. parahaemolyticus, V. vulnificus, V. mimicus, and V. fluvialis. Both Ogawa and Inaba subtypes of V. cholerae O1 serotype were found. In addition, the Hikojima subtype, which had not been previously reported in the region, was isolated in two samples. The results show that these Vibrio species are endemic in the area. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16822 J HEALTH POPUL NUTR 2013 Sep; 31(3): 314-320